(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tsoufal L. S. Emotional aspect in the formation of students’ communicative competence in teaching morphology. The article revealed the emotional aspect in the formation of the communicative competence of students offered examples of jobs that can be used in the study of the morphology.